The Rediscovery of Synchronous Reluctance and Ferrite Permanent Magnet Motors Tutorial Course Notes - Pellegrino, Gianmario; Jahns, Thomas M.; Bianchi, Nicola; Soong, Wen L.; Cupertino, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers an essential compendium on the analysis and design of synchronous motors for variable-speed applications. Focusing on synchronous reluctance and ferrite permanent-magnet (PM) synchronous reluctance machines, it provides a broad perspective on three-phase machines for variable speed applications, a field currently dominated by asynchronous machines and rare-earth PM synchronous machines. It also describes synchronous reluctance machines and PM machines without rare-earth materials, comparing them to state-of-the-art solutions. The book provides readers with extensive information on and finite element models of PM synchronous machines, including all relevant equations and with an emphasis on synchronous-reluctance and PM-assisted synchronous-reluctance machines. It covers ferrite-assisted machines, modeled as a subcase of PM-assistance, fractional slot combinations solutions, and a quantitative, normalized comparison of torque capability with benchmark PM machines. The book discusses a wealth of techniques for identifying machine parameters, with an emphasis on self-commissioning algorithms, and presents methods for automated machine design and optimization, including a software tool developed for this purpose. Addressing an important gap in the field of PM-less and less-PM electrical machines, it is intended as a self-contained reference guide for both graduate students and professional machine designers, and as a useful text for university courses on automated and/or optimized design of electrical machines and drives.
Overview of PM/Reluctance Synchronous Machine Opportunities and Challenges -- Synchronous Reluctance and PM Assisted Reluctance Motors -- PM Machine Modelling and Design -- Identification of PM Synchronous Machines Parameters for Design and Control Purposes -- Automated Design of Synchronous Reluctance Motors.
Keywords: Electric power production; Renewable energy sources; Engineering design; Electrical Power Engineering; Renewable Energy; Engineering Design